Aborto legal via telessaúde: perspectivas de mulheres em situação de violência sexual sobre um serviço de atendimento - Barbosa, Laura Turatti (2024)
Legal telehealth abortion has become an alternative for women experiencing sexual violence during the COVID-19 pandemic. Our objective was to understand the perspective of women in situations of sexual violence on the experience of legal telehealth abortion in the first public service to implement this treatment modality in Brazil. In this qualitative study, we interviewed six women, between 21 and 35 years old, who had a legal abortion via telehealth. The analysis of the results researched in four thematic categories: perspectives in relation to care via telehealth; potential and facilities of the service via telehealth; challenges and difficulties of telehealth; and continuity of telehealth service post-pandemic. The women felt supported, safe and welcomed by the professionals and the service; reporting greater ease of access to the service and treatment, and greater comfort and privacy provided by telehealth. The difficulties were related to the asynchronous format of part of the interactions, the lack of knowledge of professionals outside the service about the right to legal abortion and the dissemination of information in health networks about the service. Participants understood the continuity of the service in a post-pandemic context as viable. The results open doors to thinking about the challenges still imposed by the Unified Health System (SUS) in relation to expanding access to legal abortion, telehealth and the need for training of health professionals focused on women's human rights and person-centered practice.